If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1cos(x) + sin(2x) = 0 Multiply cos * x -1cosx + sin(2x) = 0 Remove parenthesis around (2x) -1cosx + ins * 2x = 0 Reorder the terms for easier multiplication: -1cosx + 2ins * x = 0 Multiply ins * x -1cosx + 2insx = 0 Solving -1cosx + 2insx = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2insx' to each side of the equation. -1cosx + 2insx + -2insx = 0 + -2insx Combine like terms: 2insx + -2insx = 0 -1cosx + 0 = 0 + -2insx -1cosx = 0 + -2insx Remove the zero: -1cosx = -2insx Divide each side by '-1osx'. c = 2ino-1 Simplifying c = 2ino-1
| a-11a=18 | | 4=c-2 | | 7y=5x-1 | | 97=2.1p+27.7 | | 4x-2(-2)=10 | | 9xsquared+11x-14=0 | | 9.75km=m | | 7y=2-5x | | m+20=12 | | y=-1+0.8x | | 17=15y-3 | | 2x=9x+5 | | 6x+4=2(18-x) | | 9w+9=9w+9 | | 5y=4x-5 | | 4d-3=d+9 | | 6-3c=c+8 | | 3(2x+1)=5(x+3) | | (14x-13)(5x+13)=70X^2+182 | | 8-3b=4-2b | | 8k^2+10k+3=0 | | 2(10-3x)=8 | | 10x=1.8x+32 | | 8k+10k+3=0 | | 2(2x+8)=0 | | 0=2x^2-7 | | 12+m/6=18 | | 3z+1=-11 | | -45d^7+48d^6+45d^5=0 | | 20-n=-3 | | g+11=7 | | -m^4-7m^3-12m^2=0 |